2018
DOI: 10.1177/2399808318755146
|View full text |Cite
|
Sign up to set email alerts
|

Defining urban clusters to detect agglomeration economies

Abstract: Agglomeration economies are a persistent subject of debate among economists and urban planners. Their definition turns on whether or not larger cities and regions are more efficient and more productive than smaller ones. We complement existing discussion on agglomeration economies and the urban wage premium here by providing a sensitivity analysis of estimated coefficients to different delineations of urban agglomeration as well as to different definitions of the economic measure that summarises the urban prem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 66 publications
2
54
0
1
Order By: Relevance
“…The scales vary -either 1 km 2 grid cells are utilised, where inclusion/exclusion is conducted by identifying continuous cells that match (or exceed) a certain population threshold or, in other cases, absolute numbers for territorial/administrative units are used (Vandermotten 2008;Thomas et al 2012;Fang & Yu 2017). Total population thresholds are also common, for both the core part/parts and the entire agglomeration (Czyż 2011;Cottineau et al 2018; INSEE Definition of urban unit; INSEE Definition of urban area). Migration thresholds (e.g.…”
Section: Morphological Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The scales vary -either 1 km 2 grid cells are utilised, where inclusion/exclusion is conducted by identifying continuous cells that match (or exceed) a certain population threshold or, in other cases, absolute numbers for territorial/administrative units are used (Vandermotten 2008;Thomas et al 2012;Fang & Yu 2017). Total population thresholds are also common, for both the core part/parts and the entire agglomeration (Czyż 2011;Cottineau et al 2018; INSEE Definition of urban unit; INSEE Definition of urban area). Migration thresholds (e.g.…”
Section: Morphological Approachmentioning
confidence: 99%
“…Functional interconnectivity and accessibility are also important for this approach (Fang & Yu 2017). This approach is more commonly used than the morphological one (Liang, Li & Mao 2010) and since socio-economic data is incredibly important, many studies have used various social (Thomas et al 2012) and economic (activity) indicators and their thresholds (Sykora & Mulicek 2009;Czyż 2011;Fang & Yu 2017;Cottineau et al 2018). These include, but are not limited to, GDP data, number of workplaces (mostly in the core city), income and tax data.…”
Section: Functional Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, strategies of police allocation play an important role in crime prevention and a recent discovery by Caminha et al [1] motivated us to revisit the state of the art of this subject. Caminha et al discovered a superlinear relationship [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12] between the flow of people and property crimes. In other words, the authors found that the increase of the floating population in a urban space implies a disproportionate growth of property crime in that space.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of Infrastructure for Development(World Bank 1994) are largely concerned with improving efficiency in the provision of infrastructure. Rural roads receive little attention, and rural-urban migration is hardly mentioned in any connection.3 In a broad-ranging survey of urbanization that dwells on the distinct possibility that there are too many mega-cities,Henderson (2002) emphasizes the costs of congestion and pollution.4 For extensive surveys of the theoretical and empirical literature on agglomeration economies, seeBehrens and Robert-Picoud (2016) andCombes and Gobillon (2016), respectively Cottineau et al (2016). demonstrate, using French data, that the size of agglomeration economies depends on the definition of what is 'urban'.…”
mentioning
confidence: 99%